International Livestock Research Institute One Health initiatives in Africa: Concepts and applications - Mhone, Amos L.; Akoko, James M.; Ngwili, Nicholas; Grace, Delia; Mor, Siobhan M.; Thomas, Lian F.; Roesel, Kristina; Fèvre, Eric M.; Bett, Bernard K.; Moodley, Arshnee; Knight-Jones, Theodore J.D.; Hung Nguyen-Viet (International Livestock Research Institute, 2022)
The frequency and severity of zoonotic diseases, such as the current COVID pandemic, is increasing as humans encroach on wildlife habitats, and as food production systems intensify. The One Health approach (OH) offers the best chance for solving these challenges by overcoming institutional barriers by cross-sectoral collaboration and providing stronger evidence on effective, economical, and acceptable risk management. The International Livestock Research Institute (ILRI) has various ongoing OH initiatives in collaboration with national and international partners focusing on foodborne diseases, zoonoses, emerging infectious diseases and antimicrobial resistance. The CGIAR One Health initiative (Protecting Human Health Through a One Health Approach), aims to demonstrate how One Health principles and tools integrated into food systems can help reduce and contain zoonotic disease outbreaks, improve food, and water safety, and reduce antimicrobial resistance, benefitting human, animal, and environmental health. The One Health Research, Education and Outreach Centre in Africa (OHRECA) aims to improve the health of humans, animals, and ecosystems through capacity building, strengthening of local, regional and global networks and provision of evidence-based policy advice on One Health in sub-Saharan Africa. One of the capacity-building activities is the partnership with Lilongwe University of Agriculture and Natural Resources (LUANAR) and includes co-supervision and research funding support to final year veterinary students. The CGIAR Antimicrobial Resistance Hub uses a OH approach to support efforts in low- and middle-income countries to mitigate risks of agriculture-associated antimicrobial resistance. The Hub supports the development of cost-effective interventions that are locally relevant and applicable. The CGIAR COVID 19 Hub provides a coordinated research response to the global pandemic threatening health systems worldwide, along with posing serious risks to food security; local businesses and national economies; and hard-fought progress by stakeholders at all levels towards the Sustainable Development Goals. The BUILD Uganda project supports existing livestock health initiatives by helping to scale solutions through a collaborative effort in research, extension and partnerships in Uganda. The Capacitating One Health in Eastern and Southern Africa (COHESA) initiative was set up to Increase the relevance of One Health research and policies in eastern and southern Africa, by enhancing national and sub-regional cross-sectoral collaboration, equipping educational and research institutes to train the next generation One Health workforce, and increasing the capacity to identify and deliver One Health solutions to key problems. While ILRI OH initiatives are promising and posed for success, challenges have been observed in mainstreaming ecosystem health and operationalizing OH. These are being addressed through strengthening existing research collaborations, engaging with stakeholders in food systems at all levels, and building new partnerships with ecosystem actors such as the United Nations Environment Programme.